Unearthing the Contribution of Driver Fatigue to the High Rate of Road Accidents in Zimbabwe: A Critical Analysis - Mujakachi, Tapiwa Christopher; Chitanha, Zebediah (ExcelingTech, 2025)
This study sought to investigate the contribution of driver fatigue to the rate of road accidents in Zimbabwe. The attribution of human error to 90% of fatal road accidents motivated the researchers to seek to establish the relationship between driver fatigue and the chances of it contributing to high rate of fatal road accidents which are a major disruption of the supply chain. The Theory of Planned Behaviour (TPB) was used as the anchorage theory for the study while the Theory of Reasoned Action (TRA) was the supporting theory. A Critical Realism philosophy was adopted supported by a cross-sectional design and quantitative approach. A sample of 162 participants was drawn out of a target population of 250 using random sampling from which a response rate of 63% was achieved. Data collection was done using a structured questionnaire; whilst data analysis was done using the Statistical Package for Social Sciences (SPSS) Version 22. The major finding from the study was that driver fatigue significantly contributes to the chances of drivers being involved in fatal road accidents. However, in Zimbabwe this area has been to a greater extent ignored in previous research with more attention having been directed to human error which constitutes 97% of causes of road accidents. The conclusion drawn from thus study is that while Zimbabwe’s statistics give little attention to fatigue, it might be the underlying factor of human error as reflected by meta-data from international studies. This paper contributes new insights into the need for further rigorous studies in Zimbabwe on the actual contribution of driver fatigue to fatal road accidents making use of modern technologies such as artificial intelligence (AI) and new driving technologies.